Seed-Mediated Growth Of Gold Nanorods For Diagnostic Applications. - Khoo, Khai Ling; Khairunisak, Abdul Razak; Abdul Aziz, Azlan (2010)
This work describes properties of gold nanorods synthesized using a seed-mediated method.